The web files - Palatini, Margie; Egielski, Richard (New York : Hyperion Books, 2002)
Ducktective Web and his partner try to quack the case of the pilfered peck of perfectly picked pickled peppers.
G1
Keywords: Nursery rhymes -- Fiction; Characters in literature -- Fiction; Humorous stories